Biochemical changes in progressive osteoarthrosis. Issue 5 (October 1977) - Sweet, M B; Thonar, E J; Immelman, A R; Solomon, L
Abstract : Quantitative and qualitative variations in glycosaminoglycan content were studied in fibrillated, intact, and osteophytic cartilage of the human femoral head in osteoarthrosis. Total glycosaminoglycan content was reduced in fibrillated, unchanged in intact, and raised in osteophytic cartilage. In fibrillated and osteophytic cartilage the ratio of chondroitin sulphate to keratan sulphate was high and therefore resembled immature cartilage. Hyaluronic acid was present in reduced amount in all osteoarthrotic material. Proportionally more proteoglycans were extractable by 0-15 M NaCl and 4 M guanidinium chloride from the diseased cartilage than from normal cartilage, and all proteoglycans irrespective of buoyant density were carbohydrate deficient. It is postulated that the changes described are compatible with collagen and matrix disruption due to focal overloading and the general attempt at repair.